Paul and the soul: an analysis of the Apostle's anthropology - Pluke, Dylan Hay (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
It may be no exaggeration to say that every aspect of the Apostle Paul's thought is debated. This is certainly the case for his anthropology, which is to say his beliefs regarding the nature of the human person. There is intense debate concerning what Paul believed about the human person. This is especially so when arguing about whether or not Paul believed in a human soul. In the thesis that follows, I use a linguistic analysis of Paul's writings as well as those of two of his putative backgrounds, to determine what he believed regarding the nature of the human soul. The results of this analysis are that, of the potential backgrounds that may have influenced the Apostle, the Jewish background into which he was born is the most pertinent, and that neither of the two words that Paul uses mean soul, in the sense of something which is immaterial and survives death. Rather, the psyche refers to one's life, and the pneuma to the part of the person that connects one with God and which will replace the psyche and animate the person in the new age to come.
Keywords: Paul, the Apostle, Saint -- Language; Bible -- Epistles of Paul -- Criticism, interpretation, etc; Soul -- Christianity; Soul -- Judaism; Pneuma (The Greek word); Bible and anthropology